Comprehending the Epistemic Examination of the Final and Binding Principles in Indonesia's Constitutional Court - Silalahi, Artha Debora (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
This paper critiques the dominant intercultural discourse of universally understandable and testable knowledge, focusing on the role of intersubjectivity in modern science. It argues that the validation of knowledge and the condemnation of inappropriate practices, particularly in legal contexts, are crucial in contemporary society. The study emphasizes that constitutional decisions are shaped not only by legal provisions but also by the search for values tied to truth. It explores how constitutional justice hinges on a judge’s ability to discover truth and value free from external influences. The paper also highlights the importance of legal knowledge following established rules, stressing that while judges apply legal principles and juries determine facts, legal rules must be continually critiqued to ensure just and reasonable adjudication. The research contributes to understanding the intersection of law, truth, and objectivity in the evolving landscape of constitutional decision-making.